Analisis Komunikasi Organisasi Pengurus Pramuka DKC Sidoarjo dalam Melaksanakan Program Kerja Lomba Prestasi Penegak - Hanif Ridhotin Ulya; Sufyanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The activity of the Enforcer Achievement Competition is to realize creative and highly competitive Sidoarjo scouts. The form of activities of the Enforcer Achievement Competition is the General Competition and Optional Competition. In conducting LPP activities requires good and correct organizational communication. The purpose of this study is to analyze organizational communication carried out in the LPP committee management where the communication can provide reciprocity so that the message is successfully conveyed so that the LPP committee can carry out its duties and achieve common goals. The method in this research uses descriptive qualitative method. Data was collected through interviews conducted with ten informants with the condition that the LPP committee informant. The result of organizational communication research on the management of the LPP committee is that the communication that occurs runs smoothly and effectively. Organizational communication is carried out openly so that all committees can provide ideas or ideas and all committees can work together harmoniously and all LPP administrators can provide information and manage important information in the organization that makes them able to understand the messages conveyed so that they can make decisions together with the LPP committee in order to achieve the desired goals together. The benefit of this research is to improve organizational communication among Sidoarjo DKC Scout administrators in achieving organizational goals.